Optimizing transportation of forest seedlings for the Icelandic Forest Service - Brynjar Gauti Snorrason 1992- (2020)
The Icelandic Forest Service (IFS) is responsible for transporting forest seedlings from nurseries to distribution centres, where forest farmers can pick up the seedlings assigned to them. Scheduling this transportation of forest seedlings can be complicated. Over the past years, the number of nurseries and funds for afforestation have decreased while contracts with forest farmers have increased. It is important to use available utilities to gain overview so limited resources, time and funds can be put to good use. This study analysed the transportation problem of forest seedlings in Iceland using operational research methods to design optimization models. These models can then be used as a decision support system for the IFS. The Icelandic Forest Service provided the data and information for the study. Mixed integer programming models were created, one for the current system where distribution centres are used to deliver seedlings. Another one for direct transportation where nurseries deliver the seedlings directly to the farmers. The objective was to minimize the distance travelled for the IFS and forest farmers. Different cases were studied where distribution centres were closed and new one opened. More cases were created where new nurseries were opened and supply increased to see how the results would change. The results show that the current system of using distribution centres to deliver forest seedlings is far better than delivering them from each nursery. Opening of new distribution centres might be reasonable in locations where many forest farmers close to each other have to travel long distances. Closing some distribution centres always led to more distance travelled by forest farmers. Opening of new nurseries condensed the transportation network decreasing long distance travel. Skógræktin hefur yfirumsjón með flutningum skógarplantna frá gróðrarstöðvum til dreifistöðva þar sem skógarbændur geta sótt úthlutaðar plöntur. Skipulagning flutninganna getur verið flókin í framkvæmd. Á undanförnum árum ...